Strengthening the conservation value of ex situ tree collections. Issue 3 (9th February 2015) - Cavender, Nicole; Westwood, Murphy; Bechtoldt, Catherine; Donnelly, Gerard; Oldfield, Sara; Gardner, Martin; Rae, David; McNamara, William
Abstract: With 10% of trees (> 8, 000 species) threatened with extinction there is an urgent need for botanical gardens to protect threatened trees in dedicated conservation collections. Species conservation is mentioned in the mission statements of most major botanical gardens, yet the actual conservation value of existing ex situ tree collections is low. We conducted interviews with members of the botanical garden community and organized a symposium at the 5th Global Botanic Gardens Congress to identify challenges and collect recommendations to improve living ex situ tree collections. We summarize and evaluate this information to facilitate gardens becoming more effective agents for global tree conservation. Experts agree that gardens offer valuable strengths and assets for tree conservation. Some challenges exist, however, including a lack of strategic conservation focus, collection management limitations, gaps in fundamental biological information for trees, and a lack of global coordination. Solutions are offered to facilitate gardens and arboreta of all sizes to participate more effectively in tree conservation. Prioritizing genetically diverse tree collections, participating in conservation networks, developing tree-specific conservation models and guidelines, and strengthening tree science research efforts are a few examples. Most importantly, a more coordinated global effort is needed to fill knowledge gaps, share information, and build conservation capacity in biodiversity hotspots to prevent the loss of tree species.